2015
DOI: 10.3382/ps/pev155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tryptophan supplementation on growth performance, antioxidative activity, and meat quality of ducks under high stocking density

Abstract: High stocking density (STD) could affect duck welfare and production. The objective of our study was to investigate whether dietary tryptophan (TRP) supplementation could alleviate the detrimental effects of high STD on ducks. White Pekin ducks at 4 to 6 wk of age were raised at 11 birds/m(2) and fed diets containing 0.18, 0.48, 0.78, or 1.08% TRP for 21 d. Growth performance, concentrations of TRP and metabolites in the blood and hypothalamus, antioxidative activities in serum and tissue, meat quality, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 60 publications
6
32
0
3
Order By: Relevance
“…Improved anti‐oxidant status mimics the stress in broiler chicken and ultimately facilitate to optimum weight gain and FCR. The similar results were coded by other investigations in which Liu et al () reported that in White Pekin ducks the anti‐oxidant, in terms of glutathione peroxidase (GSH‐Px) and catalase (CAT), has been increased meaningfully not only in serum and liver but also in breast muscles by dietary Trp supplementation above the NRC (1994) recommendation. Patil et al () demonstrated that the L‐tryptophan is the precursor of serotonin and melatonin and inhibited the oxidative damage in broiler birds, improved enzymatic action of catalase and superoxide dismutase.…”
Section: Discussionsupporting
confidence: 82%
“…Improved anti‐oxidant status mimics the stress in broiler chicken and ultimately facilitate to optimum weight gain and FCR. The similar results were coded by other investigations in which Liu et al () reported that in White Pekin ducks the anti‐oxidant, in terms of glutathione peroxidase (GSH‐Px) and catalase (CAT), has been increased meaningfully not only in serum and liver but also in breast muscles by dietary Trp supplementation above the NRC (1994) recommendation. Patil et al () demonstrated that the L‐tryptophan is the precursor of serotonin and melatonin and inhibited the oxidative damage in broiler birds, improved enzymatic action of catalase and superoxide dismutase.…”
Section: Discussionsupporting
confidence: 82%
“…Elevated plasma levels of hepatic enzymes such as AST and ALT in the poultry species are a sign of hepatic cell damage caused by a variety of stressors or harmful agents (Bagherzadeh‐Kasmani & Mehri, ; Miazzo et al, ; Valdivia et al, ; Yarru et al, ). On the other hand, protective action of excess dietary TRP in stressful conditions has been reported in pig (Mao et al, ; Sève, Meunier‐Salaün, Monnier, Colléaux, & Henry, ), duck (Liu et al, ), broiler chicks (Corzo, Kidd, Thaxton, & Kerr, ) and laying hens (Dong, Azzam, Rao, Yu, & Zou, ). A part of beneficial effects of excess dietary TRP may originate from de novo synthesis of its metabolites such as, for example kynurenine, 5‐hydroxytryptophan and melatonin (Le Floc’h, Otten, & Merlot, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that dietary supplementation with many nutrients possessing antioxidant activity is beneficial to meat quality. For example, arginine in pig diet, curcumin, creatine monohydrate, soybean isoflavone and tryptophan in birds' diet can improve meat quality through improving muscle antioxidative status. Reactive oxygen species (ROS) is produced as an inevitable by‐product of normal animal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle antioxidative capacity is related to meat quality, and dietary supplementation with some nutrients that have antioxidant function can enhance the quality of poultry and pork meat . Resveratrol is a natural polyphenol that can be found in various plants and has been proposed as a powerful antioxidant compound.…”
Section: Introductionmentioning
confidence: 99%